2019
DOI: 10.1108/el-03-2019-0059
|View full text |Cite
|
Sign up to set email alerts
|

A visual interactive reading system based on eye tracking technology to improve digital reading performance

Abstract: Purpose Developing attention-aware systems and interfaces based on eye tracking technology could revolutionize mainstream human–computer interaction to make the interaction between human beings and computers more intuitive, effective and immersive than can be achieved traditionally using a computer mouse. This paper aims to propose an eye-controlled interactive reading system (ECIRS) that uses human eyes instead of the traditional mouse to control digital text to support screen-based digital reading. Design/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Human-computer interaction provides interaction between humans and computers more intuitive, deep and effective than using a computer mouse [11]. Multimedia applications are an effective way to provide Education material because multimedia provides information in a variety of media, in an interactive way and creates a multi-sensory learning environment [12].…”
Section: Resultsmentioning
confidence: 99%
“…Human-computer interaction provides interaction between humans and computers more intuitive, deep and effective than using a computer mouse [11]. Multimedia applications are an effective way to provide Education material because multimedia provides information in a variety of media, in an interactive way and creates a multi-sensory learning environment [12].…”
Section: Resultsmentioning
confidence: 99%
“…Cheng et al [15] has designed a gaze-based reading annotation system that summarizes and shares a teacher's reading characteristics, such as reading speed, transitions between sections, and frequency of re-reading, to improve their students' reading comprehension. Moreover, other than inferring readers' behaviors or intent, researchers also use gaze as direct control to replace traditional input methods, such as mouse and keyboard [14,53,91]. For example, Shakil et al [91] has developed a system that allows a user to use gaze to control code navigation, such as performing "Go to Definition" by dwelling on a color square on the side of the screen, and found that gaze control can improve code reading efficiency.…”
Section: Gaze-aware Technologymentioning
confidence: 99%
“…Understanding involves knowledge and information, concepts and ideas, practical skills and intuition (Allen & McNamara, 2020). Fundamentally, it involves integrating and applying all of these in ways that are appropriate to the learner's needs Several studies have found that the use of technology enhances students' reading comprehension skills(e.g., (Alanazi, 2016;Alanazi, 2019;Chen, Wang, & Lin, 2019;Handayani, Mantra, & Suwandi, 2019;Korkmaz & Öz, 2021;Moon, Francom, & Wold, 2021)). Digital reading has several advantages over textbook reading, such as interactivity, the coverage of media and the feasibility of accessing information (Liu, 2012); in addition, reading aloud from e-books enhances performance (Davidson, Danby, Ekberg, & Thorpe, 2020).…”
Section: Relationship Between Reading and Technologymentioning
confidence: 99%